Cadherins, Selectins, and Integrins in CAM-DR in Leukemia - Kim, Hye Na; Ruan, Yongsheng; Ogana, Heather; Kim, Yong-Mi (Frontiers in Oncology, 2020)
The interaction between leukemia cells and the bone microenvironment is known to provide drug resistance in leukemia cells. This phenomenon, called cell adhesion-mediated drug resistance (CAM-DR), has been demonstrated in many subsets of leukemia including B- and T-acute lymphoblastic leukemia (B- and T-ALL) and acute myeloid leukemia (AML). Cell adhesion molecules (CAMs) are surface molecules that allow cell–cell or cell–extracellular matrix (ECM) adhesion. CAMs not only recognize ligands for binding but also initiate the intracellular signaling pathways that are associated with cell proliferation, survival, and drug resistance upon binding to their ligands. Cadherins, selectins, and integrins are well-known cell adhesion molecules that allow binding to neighboring cells, ECM proteins, and soluble factors. The expression of cadherin, selectin, and integrin correlates with the increased drug resistance of leukemia cells. This paper will review the role of cadherins, selectins, and integrins in CAM-DR and the results of clinical trials targeting these molecules.